2019
DOI: 10.3390/inorganics7110131
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic Chemistry of Nickel

Abstract: Following the discovery of the first specific and essential role of nickel in biology in 1975 (the dinuclear active site of the enzyme urease) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Nickel is an essential element for unicellular organisms and plants, being responsible for the catalytic activity of several enzymes, many involved in bacterial pathogenesis [ 92 ], and being tightly regulated intracellularly [ 93 ]. For humans, nickel is considered a dangerous metal ion, responsible of several pathologies such as immunotoxicity and cancer [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nickel is an essential element for unicellular organisms and plants, being responsible for the catalytic activity of several enzymes, many involved in bacterial pathogenesis [ 92 ], and being tightly regulated intracellularly [ 93 ]. For humans, nickel is considered a dangerous metal ion, responsible of several pathologies such as immunotoxicity and cancer [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher levels of Ni were recorded mainly in honey samples from Szczecin and its vicinity, as well as Gorzów Wlkp., whereas the concentration was below the detection limit in those for Warsaw (Figure 2). The low concentration levels of Ni in the analysed honey samples showed no effect on their quality since the toxicity of Ni at low concentrations is debatable [61,62]. Apart from Ni, it was found that Cr, Co, and Ba were also present at low concentrations in the analysed honey samples (Figure 2).…”
Section: The Assessment Of Mms Concentration In Honey Samples From Nw and Central Poland And Other Eu Countriesmentioning
confidence: 93%